Bibliometric analysis of environmental and climate change variables in palm oil production models: trends and intellectual landscapes - Duasa, Jarita; Idris, Zera Zuryana; Mohd Thas Thaker, Mohamed Asmy; Ahmad, Azlin Alisa (Universiti Kebangsaan Malaysia, 2025)
Palm oil is one of the most important global commodities, yet its production is often linked to deforestation, greenhouse gas emissions, and climate vulnerability. This raises the need to examine how environmental and climate-related factors are integrated into production efficiency models. Motivated by these sustainability concerns, this study conducts a bibliometric analysis of research published between 1989 and 2024 using the Scopus database. Bibliometric mapping techniques were applied to assess publication trends, citation impacts, co-authorship networks, and thematic shifts in the literature. The results show a consistent growth in research output, with a marked increase after 2017, reflecting heightened global attention to sustainability and climate resilience. While Malaysia and Indonesia dominate in publication volume, European and Australian institutions achieve higher citation impacts, often focusing on regulatory policies and mitigation strategies. Interdisciplinary collaboration remains limited, and systematic modelling of variables such as drought resilience and carbon sequestration is often absent. Thematic evolution highlights a transition from waste and pollution management (2006–2010) to sustainability and climate adaptation strategies (2018–2024). This study highlights key research gaps and emphasizes the need for stronger interdisciplinary collaboration, climate-resilient models, and policy-driven innovations to advance sustainable palm oil production.